(untitled) (Nigerian Journal of Technology, 2024)
Pipeline infrastructure plays a critical role in the transportation of vital resources, including oil, gas, and water. However, pipeline failures and leaks can have devastating consequences, resulting in environmental damage, economic losses, and risk to human life. Traditional methods of leak detection, such as visual inspection and pressure testing, are often time-consuming, labor-intensive, and unreliable. With the advent of wireless sensor networks (WSNs), there is an opportunity to revolutionize pipeline monitoring and leak detection. In this paper, we present a system that can monitor and detect leakage early, to enable engineers carry out prompt maintenance. This is made possible by the use of a network of nodes in a WSN, placed along a pipeline, each of which is capable of measuring and reporting varying flow rates, indicative of possible leakages. The system design consists of three major layers namely, the nodes layer, the cloud layer (for data logging), and the reporting layer. Tests were conducted under various conditions. The results show that with no leakages, the average flow rates for nodes 1, 2, 3, and 4 were 16.89747978, 16.89935602, 16.90978163, and 16.93380634 respectively. Furthermore, percentage flow rate differences of -0.02550353, 29.959675, and 30.3944134 were recorded for nodes 2, 3, and 4 respectively, after leakages occurred. The high values of the percentage difference for nodes 3 and 4 indicate a significant discrepancy in flow rate, worthy of physical inspection. The system is capable of detecting faults and leakages, even in the event of sensor failure, or network disruption.